Relationship Between Characteristics of Pregnant Women and The Degree of Anemia in the Work Area of Karya Wanita of Community Health Center (Puskesmas Karya Wanita) in the Pekanbaru City , 2023 - Susanti, Lasiah (International Journal of Healthcare Research, 2024)
Background : Anemia in pregnancy had negative effect to maternal and child health. Globally, anemia in pregnancy were 36,5%, in Indonesia it reach 44,2%. In fact, anemia in pregnancy in Indonesia were rising continually since 2017. Same phenomenon were seen in Karya Wanita Public Health Centre, where anemia in pregnancy prevalence were rise 3-4 fold in only 1 year (2022-2023). This could lead to rising rates of premature birth, low birth weight, intrauterine growth restriction, intrauterine-death, maternal, neonatal, and perinatal death. Research shown that maternal characteristics significantly correlated to pregnancy anemia. Such characteristic were mother age, educational status, working status, residence, nutritional status, financial status, gestational age, parity, interpregnancy interval. Method : In this research, the method used is quantitative with a cross sectional approach and total sampling technique. While the test used is the Spearman rank correlation test and Chi Square test with a sample of 44. Results : Factors associated with anemia in pregnancy were gestational age ( p value=0,000), parity ( p value=0,020), and nutritional status (p value=0,000). Conclusion: It can be conclude that factors related to anemia is gestational age, paritym and nutritional status.